Special electrical machines - Dhayalini, K (Anuradha Publications, 2011)
This book is designed to provide a strong foundation to the basic principles, concepts and applications of various special electrical machines. It discusses thoroughly the stepper motor, switched reluctance motor, permanent magnet DC motor, brushless permanent magnet DC motors, Brushless permanent magnet synchronous motor, synchronous motor, synchronous reluctance motor, AC commutator motor, AC series motor, repulsion motor, universal motor, and linear induction machines. This book will be helpful inproviding firm foundation on 'special electrical machines' for under graduate students of electrical engineering and post graduate students of power electronics and drives.